2018
DOI: 10.1210/jc.2017-02602
|View full text |Cite
|
Sign up to set email alerts
|

The Short Cosyntropin Test Revisited: New Normal Reference Range Using LC-MS/MS

Abstract: LC-MS/MS provides cutoff levels for cortisol and 17-OHP after cosyntropin stimulation that are lower than those based on immunoassays, possibly because cross-reactivity between steroid intermediates and cortisol is eliminated. This reduces the number of false-positive tests for AI and false-negative tests for NCCAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 21 publications
10
40
0
Order By: Relevance
“…Few data are available on cortisol concentrations measured with R2 in healthy subjects; to our knowledge, the only study to date was carried out by Ueland et al They enrolled 121 volunteers (M=F, mean age 40 years) to undergo SDCT and evaluated stimulated cortisol cut-off for R2 and LC-MS/MS (using a different spectrometer from ours). They found that the 2.5th percentile of cortisol values at 30 and 60 min following SDCT were 440 and 548 nmol/L (15.9 and 19.8 μg/dL) by R2, and 412 and 485 nmol/L (14.9 and 17.6 μg/dL) by LC-MS/MS, respectively [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few data are available on cortisol concentrations measured with R2 in healthy subjects; to our knowledge, the only study to date was carried out by Ueland et al They enrolled 121 volunteers (M=F, mean age 40 years) to undergo SDCT and evaluated stimulated cortisol cut-off for R2 and LC-MS/MS (using a different spectrometer from ours). They found that the 2.5th percentile of cortisol values at 30 and 60 min following SDCT were 440 and 548 nmol/L (15.9 and 19.8 μg/dL) by R2, and 412 and 485 nmol/L (14.9 and 17.6 μg/dL) by LC-MS/MS, respectively [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a common cut-off for the diagnosis of (primary) adrenal insufficiency, a peak cortisol concentration of less than 500 nmol/l (18 µg/dl) after stimulation is historically widely accepted [27]. However, cutoff levels for cortisol and other adrenal steroids after stimulation with cosyntropin may differ significantly based on the method used for detection (Liquid chromatography tandem mass spectrometry (LC-MS/MS) vs. immunoassay) [32]. Clinicians are strongly urged to consult with the local clinical chemist to verify the assay-specific definitions of normal cortisol responses to stimulation.…”
Section: Diagnosis Of Primary Adrenal Insufficiencymentioning
confidence: 99%
“…However a recent study proved that one should use assay specific cutoff values. We used the Roche assay for which a cut off value of 550 nmol/L is reasonable [6].…”
Section: Discussionmentioning
confidence: 99%